Charge Transport Limitations to the Power Performance of LiNi0.5Mn0.3Co0.2O2 Composite Electrodes with Carbon Nanotubes. Issue 11 (3rd November 2021) - Tambio, S. J.; Roberge, H.; Xiong, J.; Soudan, P.; Besnard, N.; Lestriez, B.
Abstract : The power performance of EV-designed LiNi0.5 Mn0.3 Co0.2 O2 (NMC 532)/PVdF/CB-CNT based electrodes with 25 mg.cm −2 active mass loading, 3.4 g.cm −3 density, 23.5% porosity and 96:1.8:2.2 wt% composition, were measured at 0 °C, 22 °C and 40 °C. The CB/CNTs ratio is 100:0 or 50:50 v%. The polarization resistance and the discharge capacity are improved by using the CB-CNTs blend especially at 0 °C and 40 °C. The shape factor of the CNTs favor the electronic wiring of the active mass at 0 °C by forming conductive bridges over the resistive grain boundaries at the surface of NMC clusters. At 40 °C, the CNTs favor both the electronic and the ionic wirings of the active mass. At this temperature, the swelling of the CB/PVdF domains could be responsible for the degradation of the electrons transfer and ions transport through the electrode. This detrimental phenomenon is mitigated with the CB/CNTs blend likely due to the CNTs shape factor.